(untitled) - Yoneyama, Shoko (London, 1999)
For large numbers of school students in Japan school has become a battle field. Recent violent events in schools, together with increasing drop-out rates and bullying are undermining stereotypes about the effectiveness of the Japanese education system. This incisive and original book looks at Japanese high school from a student perspective and contextualises this educational turmoil within the broader picture of Japans troubled economic and political life.
Keywords: Education, secondary,Education, secondary,High school students,High school students,Teacher-students relationships,Teacher-students relationships,Educational change,Educational change; Attitudes,Attitudes; Japan,Australia,Japan,Australia,Australia,Japan,Japan,Australia